Multi-omics architecture of childhood obesity and metabolic dysfunction uncovers biological pathways and prenatal determinants - Stratakis, Nikos; Anguita-Ruiz, Augusto; Fabbri, Lorenzo; Maitre, Léa; González, Juan R.; Andrusaityte, Sandra; Basagaña, Xavier; Borràs, Eva; Keun, Hector C.; Chatzi, Lida; Conti, David V.; Goodrich, Jesse; et al. (Nature communications, 2025)
Childhood obesity poses a significant public health challenge, yet the molecular intricacies underlying its pathobiology remain elusive. Leveraging extensive multi-omics profiling (methylome, miRNome, transcriptome, proteins and metabolites) and a rich phenotypic characterization across two parts of Europe within the population-based Human Early Life Exposome project, we unravel the molecular landscape of childhood obesity and associated metabolic dysfunction. Our integrative analysis uncovers three clusters of children defined by specific multi-omics profiles, one of which characterized not only by higher adiposity but also by a high degree of metabolic complications. This high-risk cluster exhibits a complex interplay across many biological pathways, predominantly underscored by inflammation-related cascades. Further, by incorporating comprehensive information from the environmental risk-scape of the critical pregnancy period, we identify pre-pregnancy body mass index and environmental pollutants like perfluorooctanoate and mercury as important determinants of the high-risk cluster. Overall, our work helps to identify potential risk factors for prevention and intervention strategies early in the life course aimed at mitigating obesity and its long-term health consequences. Obesity encompasses numerous interconnected pathological mechanisms. Here, the authors show that integrating multi-omics data uncovers distinct molecular profiles and prenatal factors linked to childhood obesity and metabolic dysfunction, providing insights for early prevention and intervention strategies.